PENDALAMAN DAN PENGEMBANGAN MATERI PAI BIDANG SKI DI SMP KELAS VII SEMESTER GENAP KURIKULUM MERDEKA - Rohbiah, Rohbiah; Barni, Mahyuddin (Berajah Journal, 2024)
This research aims to develop teaching materials for Islamic Cultural History (SKI) in grade VII junior high school according to the Merdeka Curriculum. The approach used is descriptive qualitative, with steps including literature review, analysis of teaching materials, and identification of relevant textbooks. The developed materials cover the history of the Umayyad dynasty in Andalusia, the golden age of Islam in Andalusia, the development of science during the Umayyad period, and the Islamic values that can be derived from this history. The results show that good material development should consider the criteria for content which include facts, concepts, principles, and procedures, as well as relevance to regional characteristics and student potential. Additionally, materials should be organized according to the principles of relevance, consistency, and adequacy to ensure effective and meaningful learning for students.